Lepra: fotografia e discurso na obra de Souza-Araújo (1916-1959) - Schneider, Silvia Danielle (2011)
This paper is aimed to discuss and question the book "History of Leprosy in Brazil", published in three volumes between the years 1946 to 1956, by the physician of Parana Heráclides César de Souza-Araujo, especially the second volume of his work, which portrays leprosy through images. The book, published in 1948, contains 380 prints, resulting in 1022 images. To analyze the photographs and illustrations present in the second volume, I used several books and also articles of Souza-Araujo, published in academic journals and newspapers, in order to understand what the doctor sought to build up through the composition of a volume, only with images, in such a monumental work as is the "History of Leprosy in Brazil", written to mark a form of prophylaxis of leprosy, through more than 1,600 pages. I used the writing and the imagery together, as I have understood that both complete each other, providing a better end result. I have not chosen this path because I found that the images can not be questioned without the written text, but I believe the union with other media only increases the potential of the image. Souza-Araújo built a speech, during his medical career, advocating a specific model of fight against leprosy, the isolationist, which was eventually adopted in Brazil in the early decades of the twentieth century. I analyzed the first and third volumes of "History in Brazil" to see how he built and the places in which he founded himself to write about the disease. About the second volume, the main focus of this research, I analyzed out each part of the work in depth and carefully examined each image. Soon came the interest to question photographs of patients and doctors, aiming to understand how the doctors presented each group, that shared the same space but on completely different ways even both in need of each other, are perceived in divergent ways. The first, feel the sickness in their bodies, living with it; the latter, see in a sick body a form of research, making it an object of study